Factors that Influenced People to Become Islamic Bank customer: a study on kancana VIllagers - Sari, Indah Mulia; Wibowo, Hendro; Suprapto, Edy (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2015)
Islamic finance and banking industry in Indonesia has shown a significant growth, average growth of 30% more per year in the last five years, with a total number of Islamic banks customers as much as 12 million accounts, or market share 4.8%. In this study, researchers attempt to describe the events in rural districts West Java related to the factors that influence people to become customers of Islamic banks. Data processing by tabulation and scoring and based on the analysis and discussion are carried out. The results of this study indicate that the Islamic bank customers’ data are mostly women in productive age with maximum a senior high school education and their profession up mostly are traders. Others reasearch results related to factors which influence people to become customers of Islamic banks were influenced by psychological, social, personal, economic and cultural factors.DOI:10.15408/aiq.v7i1.1360